Basal Cell Carcinomas After Radiotherapy Show More Frequent Follicular Differentiation Than Tumors From Sun-Exposed Areas: Immunohistochemical Study With a Special Focus on Infundibulocystic Basal Cell Carcinoma. (December 2022) - Cardoso, José Carlos; Alves, Francisca; Carreira, Isabel Marques; Tellechea, Oscar
Abstract: Patients submitted to radiotherapy for tinea capitis in childhood have an increased incidence of scalp basal cell carcinomas (BCCs) but also of other neoplasms, namely, follicular tumors. In a cohort of such patients, we also found a high incidence of infundibulocystic BCCs, an otherwise rare variant. We thus hypothesized that postradiotherapy BCCs could be more prone to display follicular differentiation. We compared the histological and immunohistochemical features of postradiotherapy BCCs [both conventional (16 cases) and infundibulocystic (16 cases)] with those of BCCs arising in sun-exposed areas (16 cases), using markers of follicular differentiation (PHLDA-1, CK15, CD34, β-catenin, and calretinin). Postradiotherapy BCCs showed slightly higher tendency for infundibular and/or trichilemmal differentiation than BCCs from sun-exposed areas (37.5% vs. 18.8%), but this difference was not statistically significant. Nevertheless, infundibulocystic BCCs showed more frequent expression of PHLDA-1 and stronger cytoplasmic expression of CK15 compared with the other lesions. In addition, CD34 highlighted a characteristic meshwork of stromal cells surrounding the epithelial component in all infundibulocystic BCCs, in contrast to the other postradiotherapy BCCs and UV-related BCCs, in which 78.1% were negative or only focally positive. In conclusion, our study suggests a tendency for more frequent follicular differentiation in postradiotherapy BCCs compared with BCCs from sun-exposed areas. In addition, the immunohistochemical study confirms previous data from the literature regarding infundibulocystic BCCs (higher CK15 and PHLDA-1 expression) and shows a distinctive stromal positivity for CD34 that has not been previously acknowledged in these tumors.